Denuding a Craton: Thermochronology Record of Phanerozoic Unroofing From the Pilbara Craton, Australia. Issue 9 (22nd September 2020) - Morón, Sara; Kohn, Barry P.; Beucher, Romain; Mackintosh, Vhairi; Cawood, Peter A.; Moresi, Louis; Gallagher, Stephen J.
Abstract: Cratons are ancient regions of relatively stable continental fragments considered to have attained long‐term tectonic and geomorphic stability. Low‐temperature thermochronology data, however, suggest that some cratons have experienced discrete Phanerozoic heating and cooling episodes. We report apatite fission track, and apatite and zircon (U‐Th)/He low‐temperature thermochronology data from the Archean Pilbara craton and adjacent Paleoproterozoic basement, NW Australia. Inverse thermal history simulations of this spatially extensive data set reveal that the region has experienced ~50–70°C cooling, which is interpreted as a response to the unroofing of erodible strata overlying basement. The timing of cooling onset is variable, mainly ~420–350 Ma in the southern and central Pilbara‐eastern Hamersley Basin and ~350–300 Ma in the northern Pilbara, while the westernmost Pilbara‐central Hamersley Basin does not record a significant Paleozoic cooling event. These differences are attributed to variations in sedimentary thickness and proximity to adjacent rift basins, which lack Archean age zircons in their Paleozoic strata. The onset of Paleozoic cooling coincides with the timing of the episodic intraplate late Ordovician‐Carboniferous Alice Springs Orogeny. This orogeny is thought to have resulted from far‐field plate margin stresses, which in turn caused the opening of the adjacent Canning Basin, to the north and east of the craton. We propose that basin development triggered a change of base level, resulting in denudation and the crustal cooling event reported here. Our results provide further evidence for the transmission of far‐field forces to cratons over hundreds of kilometers and support the view that cratons have experienced geomorphic changes during the Phanerozoic. Key Points: Pilbara Craton basement records a widespread cooling episode mainly between ~420 and 300 Ma resulting from denudation of a sedimentary cover Denudation is related to rifting adjacent to the craton associated with far‐field intraplate deformation transmitted over hundreds of kilometers Differences in unroofing estimates and timing are related to the thermal effect and variable thickness of the sedimentary blanket